Caracterização de vila inserida no contexto urbano - Silva, Regina Ferreira da (2008)
This dissertation initiates with a brief historical revision of Brazilian industrialization process from the end of nineteenth century on. The industrialization process, and consequence rural exodus, produced several transformations in the society, amongst them, the emergence of the so-called workers' villages with purpose of providing accommodation to the workforce and, besides that, keep them close to the industrial plant. It studies the initial occupation and the current situation of some workers' villages in both capital city and country side cities of the state of São Paulo. It demonstrates the changes that have occurred in the occupying public of this type of habitation, and also shows how both the modern urbanism and the sustainable urbanism concepts have been adapted to the new villages. In the beginning, these villages were destined to the workers' class. With elapsing of the years, they became object of search of the middle classes and average-high class. They have realized how practical is to live in these small nuclei, in downtown or near to the urban center zone, with the convenience and individuality of a house, allied to the privacy and security that this type of residential arrangement offers. That combined has increased the value of this type of housing and has stimulated the real estate market to invest in new nuclei.